Undergraduates' awareness of White and male privilege in STEM - Melissa Dancy; Katherine Rainey; Elizabeth Stearns; Roslyn Mickelson; Stephanie Moller (SpringerOpen, 2020)
Abstract Background It is well-documented that experiences in STEM courses for women and students of color are different from the experiences of White men. As part of a larger interview study, 183 college seniors from diverse gender and race backgrounds were asked their thoughts on whether the experience of being a STEM major was different for people of different races and genders. We use a framework of "science as White property", derived from critical race theory, to frame this study and results. Results White men were largely unaware of any impact of race or gender. In contrast, women of color overwhelmingly report, consistent with results from a large body of prior research, that both race and gender impact their experiences as STEM majors. Students who acknowledged race and gender impacts did not always attribute these impacts to cultural or systemic factors (i.e., some reported women are underrepresented because they are less interested in STEM rather than a structural reason). Impacts identified that were attributable to systemic factors included impacts related to being a demographic minority (i.e., intimidation, feeling out of place, feeling pressure to work harder) and/or discrimination (i.e., job discrimination, bias against women or people of color and cultural assumptions implying the superiority of White people and men). A small number of students (mostly White women) stated that women or people of color benefit from their underrepresented status, often attributing this benefit to a perception of extra encouragement and opportunities. A common theme across categorizations was that women and students of color work harder than men and White people either because they are perceived to be harder workers or as a response to the sexism and racism they encounter. Conclusions We found that White men are largely unaware of the impacts of race or gender on the pursuit of a STEM degree. Additionally, with the exception of women of color, students are less likely to perceive race as having an impact on the experiences of students than gender. We conclude with a discussion of implications for future work related to gender and race representation in STEM.